A Case Report on Carotid Artery Dissection in Hutchinson-Gilford Progeria - González-Maestro, Víctor; Monteagudo-Vilavedra , Einés; Rodríguez-Antuña , Jorge; Lendoiro-Fuentes , Marta; Gomez, Maria Soledad Brage; Mino , Elena Maside (Current Practice in Medical Science Vol. 7, 2022)
Strokes in children have their own epidemiology and aetiology, and they are frequently misdiagnosed. They exhibit some risk factors that must be recognised, much like the adult population. There are several different aetiologies and morphologies associated with cerebral arteriopathies as the cause of paediatric ischemic stroke. We report the case of a 5-year-old HGP (missense mutation—de novo— c.1822G > A in heterozygosis, LMNA gene). The patient was identified during the first year of life and had clear phenotypical characteristics. There were no additional pertinent comorbidities. Right hemiparesis with at least four hours of evolution, the inability to open the hand, and a minor decline in consciousness (pedNIHSS 5-6) led to his admission to the emergency room. Angio- and cranial-CT scans revealed evidence suggestive of left carotid dissection. On anticoagulant and antiplatelet treatment, agreement was obtained on the use of conservative medical management. The right lower limb hemiparesis and hand paresis both resolved within the first few days of the patient's treatment, and one month following discharge. Carotid dissection is indicated by the clinical symptoms, the genetic mutation's vascular phenotype, and the positioning of the radiological findings on a particular vascular morphology. Spontaneous dissections occur under a predisposing risk factor or disease and are an unusual finding in patients with Hutchinson-Gilford's Progeria.